A/B testiranje - najpreprostejša statistika za učinkovitejše spletne strani in druge poskuse - Vidmar, Gaj (Informatica Medica Slovenica, 2013)
The tutorial explains an experimentaldesign and a statistical test requiring onlyelementary-school mathematical knowledge thatare nevertheless useful in practical decisionmakingand research work. The task is to comparethe number of outcomes of one of the possiblekinds between to equally-sized groups to which theunits under observation had been randomlyassigned. The presented procedure is useful forcomparing two alternative website or userinterface designs, which is often encountered byweb/application developers (including those inmedical informatics). In the internet communitythe procedure has become known as A/B testing,but it has long been known in statistical literatureand used in various research fields ranging fromanimal behaviour studies to biomedical clinicaltrials.
Keywords: matematika; statistika; verketnost